Socially Responsible Investing in Good and Bad Times - Bansal, Ravi; Wu, Di (Andrew); Yaron, Amir (Review of Financial Studies, 2022)
Abstract We investigate the time variability of abnormal returns from socially responsible investing (SRI). Using portfolio regressions and event studies on multiple data sources, including analyst ratings, firm announcements, and realized incidents, we find that highly rated SRI stocks outperform lowly rated SRI stocks during good economic times, for example, periods with high market valuations or aggregate consumption, but underperform during bad times, such as recessions. This variation in abnormal returns of high-SR stocks vis-à-vis low SR stocks is consistent with a wealth-dependent investor preference for SR stocks that leads to an increased (decreased) demand for SRI during good (bad) times.